Endocrinological Testicular Dysfunction in Patients with Lepromatous Leprosy and the Impact of Disease on Patient's Quality of Life - Mohta, Alpana (Indian Dermatol Online J, 2020)
INTRODUCTION: Leprosy or Hansen's disease poses a drastic impact on the quality of life in affected patients even after successful completion of treatment. The involvement of the endocrine system in leprosy is usually insidious, silent, and under-reported, especially the testicular dysfunction. AIMS AND OBJECTIVES: The present study was aimed at evaluating the abnormalities of the primary testicular hormone testosterone and the gonadotrophins LH and FSH in male patients affected with lepromatous leprosy and assessing the impact of the disease on quality of life (QOL). MATERIALS AND METHODS: The study included 43 married male patients diagnosed with lepromatous leprosy. Careful history taking and examination for symptoms of testicular dysfunction were done. Serum concentrations of total testosterone, FSH, and LH were noted. The QOL was evaluated using the WHO Quality of Life-BREF (WHOQoL-BREF). RESULTS: The most common clinical manifestation of testicular dysfunction was reduced or loss of libido reported in 12 (27.9%) patients followed by gynaecomastia in 7 (16.3%). Ultrasonographic (USG) analysis revealed reduced testicular volume in 31 (72.1%) patients, and average testicular volume was 11.9 ± 4.9 mL each. Seventeen (39.5%) patients had low serum testosterone levels, 9 (20.9%) had high serum FSH level, and 11 (25.6%) high LH levels. There was a significant negative correlation between testosterone level and FSH as well as LH. There was also a significantly positive correlation between testicular volume and testosterone level. Symptomatic patients with gynaecomastia/gynaecothelia had higher hormonal derangement than those who had other symptoms. On QOL, most patients scored lowest on the domain of “social relationships” (including sexual wellbeing) followed by “psychological health”. CONCLUSION: We found a high rate of USG diagnosed testicular atrophy in lepromatous leprosy patients. Therefore, every leprosy patient should be thoroughly examined clinically to rule out features of testicular dysfunction. Testicular function tests should be routinely carried out in all leprosy patients to arrive at an early diagnosis. Leprosy is found to affect all domains of a patient's quality of life.